2020
DOI: 10.1073/pnas.2001858117
|View full text |Cite
|
Sign up to set email alerts
|

The optic nerve lamina region is a neural progenitor cell niche

Abstract: Retinal ganglion cell axons forming the optic nerve (ON) emerge unmyelinated from the eye and become myelinated after passage through the optic nerve lamina region (ONLR), a transitional area containing a vascular plexus. The ONLR has a number of unusual characteristics: it inhibits intraocular myelination, enables postnatal ON myelination of growing axons, modulates the fluid pressure differences between eye and brain, and is the primary lesion site in the age-related disease open angle glaucoma (OAG). We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…These findings are of relevance, as Bernstein et al recently demonstrated that the optic nerve lamina region (ONLR) contains a neural progenitor cell (NPC) niche, which may have a role in both postnatal optic nerve development and in adult optic nerve support and repair [56]. Unmyelinated retinal ganglion cell axons originating in the retina pass through the ONLR, the most anterior portion of the optic nerve, before myelination occurs in the more distal portion of the optic nerve.…”
Section: Visible and Far-red To Near-infrared Photobiomodulation In Neuronal Differentiationmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings are of relevance, as Bernstein et al recently demonstrated that the optic nerve lamina region (ONLR) contains a neural progenitor cell (NPC) niche, which may have a role in both postnatal optic nerve development and in adult optic nerve support and repair [56]. Unmyelinated retinal ganglion cell axons originating in the retina pass through the ONLR, the most anterior portion of the optic nerve, before myelination occurs in the more distal portion of the optic nerve.…”
Section: Visible and Far-red To Near-infrared Photobiomodulation In Neuronal Differentiationmentioning
confidence: 96%
“…Unmyelinated retinal ganglion cell axons originating in the retina pass through the ONLR, the most anterior portion of the optic nerve, before myelination occurs in the more distal portion of the optic nerve. However, the precise sites of postnatal RGC axonal growth and the mechanism by which myelination occurs at sites of newly formed axonal membrane late in postnatal growth are still obscure [56]. It is well known that ONLR has a number of unusual characteristics: it inhibits intraocular myelination, enables postnatal optic nerve myelination of growing axons, modulates the fluid pressure differences between eye and brain, and is the primary lesion site in age-related open-angle glaucoma.…”
Section: Visible and Far-red To Near-infrared Photobiomodulation In Neuronal Differentiationmentioning
confidence: 99%
“…Cells from regions of the adult retina such as the retinal pigment epithelium (RPE) [47,48], CE [49][50][51][52][53], Müller glia cells [51,[54][55][56], iris pigment epithelium [57,58] and optic nerve [48] show stem cell characteristics to varying degrees (Figure 2C). Among them, the CE and Müller glia are identified as two main retinal stem cell sources.…”
Section: Adult Retinal Stem Cellsmentioning
confidence: 99%
“…A subpopulation of adult human RPE cells is capable of being activated to become RPE retinal stem cells in vitro and differentiated into multipotent stable RPE or mesenchymal lineages [47]. The optic nerve lamina region (ONLR) in both humans and mice contains a retinal NPC niche [48]. Adult NPCs in the ONLR exhibit multipotency and generate two types of glia: astrocytes and oligodendrocytes.…”
Section: Adult Retinal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation